T2–T2 exchange in biofouled porous media - Hornemann, Jennifer A.; Codd, Sarah L.; Romanenko, Konstantin V.; Seymour, Joseph D. (Diffusion Fundamentals, 2009)
Recent two dimensional nuclear magnetic resonance (NMR) techniques access exchange in pore structures through surface relaxation and diffusion based relaxation [1-4]. This research applies these techniques to measure pore changes due to biofilm growth and the impact this growth has on diffusion transport. The porous media used in this study are model beadpacks constructed from borosilicate glass beads with diameters approximately 100 um. This research shows that through changes in the relaxation rates, NMR can be used to verify biofilm growth in porous media.